1035325 Karakteristik Kejadian Persalinan Sectio Cesarea di Rumah Sakit Fadhilah - Ana Sapitri (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2019)
ABSTRACT Cesarean section is a surgery to give birth to a child through apdomen inisi on the wall of the uterus, which is influence by several factors: age, location of the abnormality, height ( physical causes), activity imitation, restriction of foot/ strict diet and psychological condition from the results of research in RS Fhadilah Prabumulih carriying 123 people who give birth by cesarean section action. The purpose of this study was to determine is there are relationship between malpresentasi, mothers height and prolonged labor with the insidens of cesarean section in RS Fadhilah Prabumulih years 2019. This study uses an approatch survei metod with cross sectional analytic by using secondary data. Statistical test in use is a Chi square statistical test by using SPSS statistical computerized system. The study population was all women giving birth in RS Fadhilah Prabumulih years 2018, so that in a population get is 779 people. The results of the data analisis with statistical test Chi Square generate p value= 0,318 < 0,05 indicates no correlation between malpresentasi with cesarea seksio action whereas in height mothers with childbirth seksio cesarea also obtained p value= 0,000 < 0,05 indicates there is a relationship between malpresentasi with labor sekstio cesarean and the prolanged labor with labor sektio cesarean obtained p value 0,128 show no relationship from the results of this research can be conluded that there are three independen variables ( malpresentasi, prolonged, labor and height) is partially to do with cesarea seksio action and simultaneosly there is a significant correlation between malpresentasi, prolonged labor and height. With seksio action cesarean at home RS Fadhilah Prabumulih. To the Directur RS Fadhilah Prabumulih in order to improve maternity services to the actio sectio cesarean. Keywords:cesarea section, Malpresentation, height and old parturition.